Federico García Lorca : the poetry in all things - Bonaddio, Federico (Icons of the Luso-Hispanic world, 2022)
"Feted by his contemporaries, Federico García Lorca's status has only grown since his death in 1936: poet, playwright, political martyr, gay icon, champion of women, defender of the oppressed. This book guides readers through the key themes and concerns in Lorca's work. It demonstrates how Lorca applied his poetic sensibilities and lyrical craft to what were, in essence, tangible, real-life issues: the plight of Andalusia's Romani people, the idea of modernity and the condition of women in Spain. What becomes evident is that, even though he was writing at a time when many writers and artists were less inclined to deal directly with the things of the world, Lorca maintained a profound interest in the human subject and in the world around him. It is this interest, the book argues, in tandem with his poetic vision and craft, that ensured his most popular works' enduring, universal appeal."--